Gerontology and Social Education: senior universities in the world and the portuguese model of U3A - Jacob, Luis (2020)
This book aims to learn about the development and characterization of the education for seniors, in particular the senior universities (U3A) and the possible impact they can have on their regulars. Senior universities are a lifelong education project, involving more than 100 countries, thousands of organizations and teachers and millions of students. The positive influence of these organizations in the lives of seniors is well known. The data reveal an improvement in the perception of students' physical and mental health status; increase in the number of social contacts and consequently decrease in the feeling of loneliness; there was a reduction in the antidepressant medication taken; depression levels are substantially lower than in the general population; the level of knowledge has increased, practically in the digital area, self-esteem has risen, and students feel more active and better inserted in the community. U3A worldwide have nearly two models, French and English, which does not prevent the emergence of hybrid models. In this book, we will address some issues related to ageing and lifelong education or life long learning, as well as making a short history of the emergence of U3A in the world and how they currently organized. In the end, we will discuss in more detail the U3A in Portugal. Through this study, it concludes that the senior universities in Portugal which follow the English model were created essentially by associations, after the year 2000, on average have a paid employee and work mostly in assigned facilities. Senior universities are attended mainly by women, aged 65-75, retired or domestic, married, from all socioeconomic backgrounds and with varying degrees of education. They attend an average of four subjects weekly and go three days a week. Professors are of all ages, mostly with higher education, give 2 hours of classes per week, also represented by retired and active people, are very satisfied with their volunteering at senior universities and the main motivations presented are the joy of teaching and helping others. The Portuguese senior universities are present basically on the entire national territory, are born of civil society, are an example of volunteering and contribute to improving the quality of life of seniors.